Farewells at HEP - Dim, AJ (Universiti Teknologi MARA, Sarawak, 2006)
In conjunction with the farewell ceremony for En. Khalid Ibrahim and Cik Haryati, the Student Affairs Department (HEP) organized a breaking of fast buffet and prayers at Kolej Seri Gading 3A on 27th October 2005. En. Khalid Ibrahim, the former HEP Assistant Registrar who switched profession to become a full time lecturer while Cik Haryati who resigned after being with UiTM Sarawak for a couple of months. The buffet and prayers took place at the study room and ’surau' of Kolej Seri Gading 3A. It was attended by UiTM administrative staff from the various sections in Student Affairs Department. The guest of honor was the UiTM Assistant Director for Sudent Affairs, Prof. Madya Dr. Abang Ahmad Ridzuan Abang Awit.